2000
DOI: 10.1046/j.1365-2486.2000.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield response of Lolium perenne swards to free air CO2 enrichment increased over six years in a high N input system on fertile soil

Abstract: Summary After a step increase in the atmospheric partial pressure of CO2 (pCO2), the availability of mineral N may be insufficient to meet the plant's increased demand for N. Over time, however, the ecosystem may adapt to the new conditions, and a new equilibrium may be established in the fluxes of C and N. This would result in a higher dry mass (DM) yield response of the plants to elevated pCO2. The effect of elevated atmospheric pCO2 (60 Pa pCO2) was studied in Lolium perenne L. swards with two N fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…In low N swards (14 g N m K2 y K1 ), nitrate was probably limiting for NDP in close proximity to roots because of plant uptake, and so competition would have arisen between NDP and Lolium plants for available N. Additionally, greater plant N demand (Daepp et al, 2000) or microbial immobilisation (Hungate et al, 1997) would have further reduced nitrate availability for NDP as indicated by lower available soil nitrate in the high N swards under elevated pCO 2 (Table 1).…”
Section: Frequency Of Nitrate Dissimilating Pseudomonasmentioning
confidence: 99%
“…In low N swards (14 g N m K2 y K1 ), nitrate was probably limiting for NDP in close proximity to roots because of plant uptake, and so competition would have arisen between NDP and Lolium plants for available N. Additionally, greater plant N demand (Daepp et al, 2000) or microbial immobilisation (Hungate et al, 1997) would have further reduced nitrate availability for NDP as indicated by lower available soil nitrate in the high N swards under elevated pCO 2 (Table 1).…”
Section: Frequency Of Nitrate Dissimilating Pseudomonasmentioning
confidence: 99%
“…The C and T plots received 14 g m )2 y )1 N, NH 4 NO 3 , (at the beginning of the season, and then after each cut, except for the last). This amount is limiting for plant growth [14]. M. coerulea plants (noted M) originated from a littoral meadow located at the southern shore of Lake Neuchâtel (Cudrefin, Switzerland).…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…These results suggest that PNL could have prevented soil C sequestration under elevated CO 2 in the Swiss FACE experiment. However, only the L. perenne system receiving low N fertilization rates and elevated CO 2 appeared limited by N availability (Daepp et al 2000). In the L. perenne systems receiving the high N fertilizer treatment, biomass production had increased by 28%.…”
Section: Microbial Activitymentioning
confidence: 99%